The effect of peatland drainage and rewetting (ditch blocking) on extracellular enzyme activities and water chemistry. (21st August 2014) - Peacock, M.; Jones, T. G.; Airey, B.; Johncock, A.; Evans, C. D.; Lebron, I.; Fenner, N.; Freeman, C.
Abstract Extensive areas of European peatlands have been drained by digging ditches in an attempt to improve the land, resulting in increased carbon dioxide fluxes to the atmosphere and enhanced fluvial dissolved organic carbon (DOC) concentrations. Numerous peatland restoration projects have been initiated which aim to raise water tables by ditch blocking, thus reversing drainage‐induced carbon losses. It has been suggested that extracellular hydrolase and phenol oxidase enzymes are partly responsible for controlling peatland carbon dynamics and that these enzymes are affected by environmental change. The aim of this study was to investigate how drainage and ditch blocking affect enzyme activities and water chemistry in a Welsh blanket bog, and to study the relationship between enzyme activity and water chemistry. A comparison of a drained and undrained site showed that the drained site had higher phenol oxidase and hydrolase activities, and lower concentrations of phenolic compounds which inhibit hydrolase enzymes. Ditch blocking had little impact upon enzyme activities; although hydrolase activities were lowered 4–9 months after restoration, the only significant difference was for arylsulphatase. Finally, we noted a negative correlation between β‐glucosidase activity and DOC concentrations, and a positive correlation between arylsulphatase activity and sulphate concentration. Phenol oxidase activity was negatively correlated with DOC concentrations in pore water, but for ditch water phenol oxidase correlated negatively with the ratio of phenolics to DOC. Our results imply that drainage could exacerbate gaseous and fluvial carbon losses and that peatland restoration may not reverse the effects, at least in the short term.